Russia’s Network Diplomacy in Eurasia: From the EAEU to the Greater Eurasian Partnership - Valeriia I. Bulva; Alexander K. Bobrov (Vestnik RUDN. International Relations, 2025)
The present study is of particular pertinence in the context of the transformation of the mechanisms of diplomatic interaction that has occurred in the wake of the expansion of the composition of participants and the diversification of the areas of international cooperation. In this regard, the Russian Federation seeks to use the potential of network diplomacy to establish a dialogue with interested partners from among like-minded states and representatives of the non-governmental sector. The purpose of the study is to assess the prospects for the development of Russia’s network diplomacy in Eurasia as a key tool for establishing ties with regional and extra-regional (“external contour”) actors. The scientific novelty of the study lies in the fact that using the example of the Eurasian region the authors comprehensively consider various institutions and mechanisms of network interaction - from broad-profile regional formats to highly specialized working groups on specific tracks. The analysis is based on a systems approach. The article includes an in-depth study conducted with the use of the institutional research method of various formats of network diplomacy, including flexibility, lack of hierarchy and openness. It was revealed that in Eurasia Russia is able to address multiple issues concurrently through the network diplomacy. Firstly, such diplomacy is required at the initial stage of development of integration processes and is based on the model of multi-speed and multi-level integration, as evidenced by the Eurasian integration paradigm prior to the establishment of the Eurasian Economic Union (EAEU). Secondly, network diplomacy is aimed at deepening sectoral cooperation within the framework of working groups of regional structures - the EAEU and the Shanghai Cooperation Organization (SCO), uniting government experts and representatives of the non-governmental sector. Thirdly, in the post-Soviet space, including Eurasia, Russia tested such network diplomacy tools such as conflict resolution formats. Fourthly, the potential of network diplomacy is important to form a single integration contour in Eurasia. The authors conclude that network diplomacy in Eurasia plays an important role in creating additional opportunities for equal dialogue with member states of regional multilateral structures and other interested countries, including the countries of the Association of Southeast Asian Nations (ASEAN) and the SCO. It facilitates the prevention of the risk of fragmentation of Eurasia. In this regard, the most promising course of action appears to be the promotion of the Greater Eurasian Partnership initiative - a project that accumulates the potential and resources of states, multilateral associations (EAEU, SCO, ASEAN) and initiatives of individual regional actors (Belt and Road Initiative).